The Intersections between Self-Deception and Inconsistency: An Examination of Bad Faith and Cognitive Dissonance - Bahnmiller, Hannah (Stance: an international undergraduate philosophy journal, 2015)
The relationship between the concepts of bad faith, coined by Jean-Paul Sartre, and cognitive dissonance, developed by Leon Festinger, is often misunderstood. Frequently, the terms are over-generalized and equivocated as synonymous ideas. This paper attempts to clarify the intricacies of these two concepts, outlining their similarities and differences.